Pembinaan Penambangan Emas Skala Kecil dan Masyarakat Lingkar Tambang Emas di Desa Cisarua, Bogor - Irfan Marwanza; Masagus Ahmad Azizi; Riskaviana Kurniawati; Wiwik Dahani; Subandrio Subandrio; Taat Tri Purwiyono; Suherman Dwi Nuriana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
The Trisakti University Community Service Program (PKM) was carried out in Cisarua Village, Nanggung District, Bogor Regency, West Java, in collaboration with the local Regional Government. Stakeholder partners served as facilitators for this project, which aimed to socialize and establish sustainable mining practices for miners and communities around gold mines. Cisarua Village, located in Nanggung Regency, is known for having potential mineral resources, particularly gold deposits, which are often collected by mining communities both individually and collectively. However, this mining activity has major negative effects, leading the government to stop it, one of which being its damaging environmental impact. Environmental issues and land conditions following gold mining provide significant risks and concerns, including mercury and cyanide contamination, which are harmful to human life and the surrounding environment. One of the most significant issues has been the lack of reclamation of mine holes caused by human mining activity. Based on these issues, the team demonstrated the public on good and correct mining practices (GMP). The team is collaborating with local communities and governments to develop ways to predict future implications of gold mining activities. PKM activities are carried out by offering materials and discussions that have proven effective in developing community knowledge. The survey of 25 respondents showed that a greater understanding of good mining practices. Survey results show that previously 61% of respondents did not understand about GMP. After implementing education and training through PKM, there was an increase of 11% in understanding of GMP. This shows the effectiveness of the program in increasing awareness and knowledge about good and correct mining practices among participants.